2015
DOI: 10.2807/1560-7917.es.2015.20.37.30018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, genotyping and macrolide resistance of Mycoplasma pneumoniae among isolates of patients with respiratory tract infections, Central Slovenia, 2006 to 2014

Abstract: In this retrospective study we employed real-time polymerase chain reaction (PCR) to analyse the occurrence of Mycoplasma pneumoniae among upper and lower respiratory tract infections (RTI) in the Central Region of Slovenia between January 2006 and December 2014. We also used a culture and pyrosequencing approach to genotype strains and infer their potential macrolide resistance. Of a total 9,431 tested samples from in- and out-patient with RTI, 1,255 (13%) were found to be positive by M. pneumoniae PCR. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…Based on these data, we assume that the macrolide-resistant strains have developed in the southern or northern China. On the other hand, in Western countries, the proportion of resistant bacteria has been relatively low, ranging from 1% to 10% [10,16,32,38]. This phenomenon is mainly owing to the careful use of macrolides in these areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these data, we assume that the macrolide-resistant strains have developed in the southern or northern China. On the other hand, in Western countries, the proportion of resistant bacteria has been relatively low, ranging from 1% to 10% [10,16,32,38]. This phenomenon is mainly owing to the careful use of macrolides in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…This periodicity in M. pneumoniae infection may be related to changes in the sequence of P1 adhesin, which is the main method of M. pneumoniae typing. According to the differences in the sequence of P1 adhesin gene MPN141, M. pneumoniae is divided into P1 type I and P1 type II with several subtypes [16,17]. The prevalence of M. pneumoniae subtypes differs between countries and years, and the dominance of one subtype is followed by the dominance of another M. pneumoniae subtype [18].…”
Section: Introductionmentioning
confidence: 99%
“…P1 is a primary immunogenic component of M. pneumoniae , and thus sequence variation within the P1 gene can be expected to result in alteration in the surface-exposed protein thereby potentially affecting the infectious process. In fact, the alternating predominance of types 1 or 2 strains circulating in a population during epidemic seasons has been documented previously ( Lind et al, 1997 ; Kenri et al, 2008 ; Kogoj et al, 2015 ), and the cyclic pattern was potentially attributed to the development of temporary immunity to one type, thus allowing reemergence of the other type ( Dumke et al, 2004 ). However, recently co-circulation of both P1 types and multiple variants have been reported during the same epidemic period and even during discrete outbreaks ( Waller et al, 2014 ; Diaz et al, 2015b ; Jacobs et al, 2015 ).…”
Section: Characterization Of M Pneumoniaementioning
confidence: 59%
“…As a consequence of these findings and because of the dominant role of antibodies to the P1 protein in sera of infected patients, it has been suggested that type-specific immunoglobulins have an influence on subsequent re-infections in affected individuals as well as on the epidemiology of infections in greater populations. The results of different studies confirmed that the epidemic peaks of respiratory infections due to M. pneumoniae occurring at intervals of 3–7 years were correlated with a change of the predominant p1 type ( Kenri et al, 2008 ; Kogoj et al, 2015 ; Suzuki et al, 2015 ; Zhao et al, 2015 ). In other investigated populations, significant differences in the proportion of types 1 and 2 strains during endemic and epidemic periods of infections were not detected ( Dumke et al, 2015 ; Jacobs et al, 2015 ).…”
Section: Genotype-specific Immune Response and Influence On The Epidementioning
confidence: 59%